Penarapan Metode Korelasi dalam Mengukur Hubungan antara Customer Relationship dengan Customer Loyality Pada PT Antika Raya Surabaya - I Putu Artaya; I Gede Arimbawa (BISMA (Bisnis dan Manajemen), 2018)
This research focus on application of customer relationship management in relation with customer loyality. Object of this research is PT Antika Raya Surabaya, because this company had appropriate characteristic with this method. Data is base on quesioner, with 30 respondance who live in Surabaya and customer of his company.According to result of signification test, correlation between all customer variables of customer relationship management with customer loyality has real relation or signification between customer variable relationship with customer loyality.